Research in technology education: Looking back to move forward - Williams, John (Kluwer Academic Publishers, 2013)
This paper attempts to summarize the focus of the research that has recently taken place in Technology Education, and from that basis suggest a trajectory for future research trends. Some research that is considered particularly seminal to the profession is summarised, and the paper is concluded with some reflections about personal research agendas.